Γ−Carboxyethyl hydroxychroman, a metabolite of γ−tocopherol, preserves nitric oxide bioavailability in endothelial cells challenged with high glucose. Issue 18 (December 2016) - Li, Youyou; Bharath, Leena P; Qian, Ying; Ruan, Ting; Anandh Babu, Pon Velayutham; Bruno, Richard S; Symons, J David; Jalili, Thunder
Endothelial dysfunction occurs when there are imbalances between factors that regulate the synthesis and degradation of nitric oxide (NO ), and has been reported in patients with hyperglycemia and insulin resistance. We reported that supplementation with γ-tocopherol (γ-T) in humans limits impairments in endothelial function otherwise induced by postprandial hyperglycemia. Given the rapid metabolism of γ-T into γ-carboxyethyl hydroxychroman (γ-CEHC), we hypothesized that the vasoprotective activities of γ-T could be attributed to its metabolite γ-CEHC. To test this, human aortic endothelial cells (HAECs) treated with 0 (vehicle control) or 3 µM γ-CEHC for 24 h prior to incubation with normal (5 mM) or high (25 mM) glucose for 48 h. High-glucose increased levels of uncoupled endothelial nitric oxide synthase (eNOS) as evidenced by reduced ( p  < 0.05) eNOS dimer:monomer. High glucose also prevented insulin-stimulated increases in p-Akt Ser473 : total Akt, p-eNOS Ser1177 : total eNOS, and NO production. These adverse changes were accompanied by increased ( p  < 0.05) reactive oxygen species and mRNA expression of inflammatory mediators (VCAM-1, E-selectin, IL-8). However, each deleterious response evoked by high glucose was prevented when HAECs were incubated with γ-CEHC prior to the high glucose challenge. Taken together, our data support the hypothesis that vascular protection provided by γ-T in vivo may be elicited through the bioactivity of its metabolite, γ-CEHC. Furthermore, it is possible that the antioxidant and anti-inflammatory activities of γ-CEHC may mediate this protective activity.